Kawasaki Disease presenting with intussusception: a case report - Hussain Rumana N; Ruiz Gary (BMC, 2010)
Abstract A 3 yr old boy presented with abdominal pain, fever and red jelly stools. Intussusception was diagnosed and effectively reduced with air insufflation. However, despite an improvement in his clinical condition, the child remained febrile and miserable; 5 days later he developed characteristic signs of Kawasaki disease and was treated with intravenous immunoglobulin and high dose aspirin with good results. Intussusception prior to the typical features of Kawasaki disease has not been described previously in the English literature. This case illustrates a novel presentation of Kawasaki disease.